Do flow volume loops alter surgical management in patients with a goitre?. (7th August 2014) - Stevens, J.L.; Constantinides, V.; Todd, J.; Meeran, K.; Christakis, I.; Tolley, N.S.; Palazzo, F.F.
Summary Introduction Flow volume loops (FVLs) are considered part of the workup of patients with thyroid enlargement presenting to the endocrinology clinic. They are used to detect upper airway obstruction (UAO) secondary to tracheal compression (TC) from a goitre. Surgical assessment in contrast tends to focus on clinical evaluation supplemented when required by imaging. The aim of this study was to investigate whether FVLs influence the decision to operate in patients with a goitre. Methods We identified patients with a goitre referred by the department of endocrinology for FVLs between 2006 and 2011. The results of the FVL were collated, and their impact on patient management was assessed. Results Ninety‐six patients were referred for FVL. In 38 patients, the indication was specifically to evaluate the effects of a goitre. Of these, 33 were reported as normal. Five FVLs were reported as abnormal (3 suggesting lung pathology and 2 TC). Both patients with TC on FVL presented no CT evidence of TC and underwent surgery due to abnormal cytology. Of the 33 normal FVLs, 7 underwent surgery: 2 for local compression, 4 for abnormal cytology and 1 for Graves' disease. None of the FVLs influenced the decision to operate. Conclusion FVLs may detect subradiological TC, but rarely influence management in patients with a goitre. In view of this and the cost of £235 per investigation, FVL should be reserved for goitre patients with suspected primary lung pathology, where the distinction between large and small airway compression is likely to influence management.